AN INNOVATION OF HIGH PERFORMANCE CONCRETE BY REPLACING CEMENT WITH NICKEL SLAG POWDER - Bunga Yubi Nabiilah; Lisa Oksri Nelfia; Sotya Astutiningsih (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2019)
ABSTRACT Nickel slag is a solid waste produced from the nickel smelting process. At present, In Indonesia, the total capacity of domestic nickel smelting reaches 5 million tons/year with the assumption of NPI or FeNi production with a Ni level of 10%, requiring the input of Ni ore raw materials around 40 million tons/year in which around 30 million tons will become waste/slag. Currently, the area of Southeast Sulawesi has a potential of huge nickel resources of 97.4 billion tons, which spread over 480 thousand hectares of land. This has led to a continuous increase in the demand of concrete towards infrastructural development in Indonesia. Therefore, the aim of this research is to reuse nickel slag powder in the context of environmentaly friendly by analyzing the tensile strength using nickel slag powder (NSP) as a cement substitution material for the manufacture of high-performance concrete. Specimens were made with water-cement ratio of 0.31 and compared with 100% OPC Type 1 cement (as reference). Furthermore, the NSP substitution of cement were 5%, 10%, 15%, 20%, 25% and 30% with a concrete age of 3, 7, 14 and 28 days. Analysis of physical characteristics of nickel slag powder and cement were carried out by using the Le Chatelier method, while the mechanical characteristics comprised ease of work in the field (workability) and split tensile strength. The manufactured concrete was made by using Sika Viscocrete 8015 superplasticizer admixture with split tensile strength test results for NSP substitution at 28 days ≥ 5% of the value of compressive strength. Keywords: High-performance concrete, Nickel slag powder, Split tensile strength,